G417(P) Unexplained multiple rib fractures in a hospitalised child. Lessons from a serious case review. (7th April 2014) - Allen, M; Aziz, M
Abstract : Background: We describe the unusual case of a three month old girl who developed six posterior rib fractures whilst an inpatient on a paediatric ward with a paroxysmal cough. Causality of rib fractures detected in children include non-accidental injury, bone fragility and trauma. A serious case review investigates the contributory factors resulting in this unexplained injury and lessons to be learnt for us in our clinical practice. Objective: We present the case of the three month old girl with a ventricular septal defect who had unexplained multiple posterior rib fractures occurring whilst an inpatient for H1N1 influenza. A serious case review explores the cause for these fractures and highlights the lessons learnt from this case. Methods: We performed an extensive literature search to explain causes of rib fractures in children including paroxysmal cough and chest physiotherapy related fractures. Examining the full case notes, imaging and serious case review of this baby we have been able to document a full case report of this unexplained rib fractures and explore the causality. Results: No single cause for the rib fractures was determined. Non-accidental injury was fully investigated and thought to be unlikely, as was chest physiotherapy related rib fractures which mainly occur laterally. No previous cases have been described in medical literature of multiple rib fractures in a child due to a paroxysmal cough. Contributory factors include prematurity, severe paroxysmal cough, prolonged diuretic use, sub optimal nutrition and bone density. Outcomes of this serious case review highlight the importance of regular senior reviews of longstay patients with regular appraisal of nutritional status and regularly updated social history including parental involvement and capacity. Conclusions: As this is a unique presentation of multiple rib fractures in a hospitalised patient it is important for it to be reported. This enables paediatric doctors to be aware of possible contributory factors in causes of occult rib fractures. It also makes our conclusions from the serious case review transparent to allow other paediatric departments to minimise risks of this occurring again.